Negative pressure wound therapy with instillation and dwell time (NPWTi-d) with V. A. C. VeraFlo in traumatic, surgical, and chronic wound: a helpful tool for decontamination and to prepare successful reconstruction - Diehm, Yannick; Loew, Julia; Will-Marks, Patrick; Fischer, Sebastian; Hundeshagen, Gabriel; Ziegler, Benjamin; Gazyakan, Emre; Kneser, Ulrich; Hirche, Christoph (International wound journal, 2020)
For nearly two decades, Negative Pressure Wound Therapy (NPWT) has been used for temporary wound coverage as well as wound bed preparation. The addition of instillation and dwell time as an adjunct to NPWT (NPWTi-d) enables wound bed cleaning and improved wound bed granulation. Thirty patients with different types of colonised wounds (traumatic, surgical, and chronic) were treated with NPWTi-d using saline for instillation. Patient data, microbiological data and wound characteristics were collected and analysed. Endpoints were bacterial decontamination (count and type), effect on wound bed granulation, and successful reconstruction. Additionally, subgroup analyses for traumatic, surgical, and chronic wounds as well as patients pretreated with conventional NPWT or isolated gram-positive or negative germs were performed. NPWTi-d was applied on average for 13 days with a total hospitalisation time of 51 days. After NPWTi-d, decontaminated wounds were detected in 23% of cases. The number of different bacteria as well as bacterial count could be significantly reduced from 2.38 to 1.16 and 3.9 to 1.3, respectively. This was similar for all subgroups except surgical wounds, in which NPWTi-d did not lead to a significant reduction of the bacterial count. NPWTi-d resulted in a significant stimulation of granulation tissue. Successful reconstruction was achieved in 90% of cases. NPWTi-d enabled wound pre-conditioning by powerfully reducing or decontaminating the bacterial load and spectrum in most of the wounds. The wound bed integrity was re-established to prepare successful reconstruction.
First published: 27 July 2020
Gesehen am 19.08.2021